2021
DOI: 10.1186/s40170-021-00240-1
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 enhances oxidative phosphorylation in breast cancer and promotes mammary tumorigenesis in mice

Abstract: Background Sirtuin 6 (SIRT6) is a NAD+-dependent deacetylase with key roles in cell metabolism. High SIRT6 expression is associated with adverse prognosis in breast cancer (BC) patients. However, the mechanisms through which SIRT6 exerts its pro-oncogenic effects in BC remain unclear. Here, we sought to define the role of SIRT6 in BC cell metabolism and in mouse polyoma middle T antigen (PyMT)-driven mammary tumors. Methods We evaluated the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 51 publications
0
24
1
Order By: Relevance
“…It was reported that NAD (NAD + and NADH) concentrations decreased both in blood and tissues (including liver, kidney, stomach, cerebrum, lung, spleen, and large and small intestine) when mice were fed a NiA-free diet [26]. It was also reported that NADH together with SIRT protein promote tumorigenesis [27]. It could be assumed that PABC disease influences NAD(P)H in blood as well.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that NAD (NAD + and NADH) concentrations decreased both in blood and tissues (including liver, kidney, stomach, cerebrum, lung, spleen, and large and small intestine) when mice were fed a NiA-free diet [26]. It was also reported that NADH together with SIRT protein promote tumorigenesis [27]. It could be assumed that PABC disease influences NAD(P)H in blood as well.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, OXPHOS plays a role in the pathophysiology of cancers including breast cancer (Zu and Guppy, 2004;Vaupel and Mayer, 2012;Ippolito et al, 2016;Ashton et al, 2018;Ikeda et al, 2019;Schöpf, et al, 2020;Takayama et al, 2020;Becherini et al, 2021). In fact, overexpression of mitochondrial OXPHOSrelated proteins including cytochrome c oxidase subunit 4 (COX4) has been identified in breast cancer cells (Calderón-González et al, 2015).…”
Section: Oxphos and Mitochondrial Respiratory Genes Contribute To Breast Cancer Biologymentioning
confidence: 99%
“…PDHC is essential for glucose oxidation through its ability to promote a switch from the glycolytic to the oxidative pathway and the subsequent use of substrates through the respiratory chain in mitochondria. PDHC catalyzes the oxidative decarboxylation of pyruvate, yielding NADH and acetyl-CoA, key molecules for mitochondrial ATP generation ( 48 ). During sepsis, the downregulation of PDHC might contribute to energy metabolism disturbances by impairing the capacity of mitochondria for energy production.…”
Section: Pathological Effect Caused By Pdh Imbalancementioning
confidence: 99%